Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galvàn, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V (Journal of Proteome Research, 2013)
Responses to drought stress by water withholding have been studied in 1 year old Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) seedlings from seven provenances from Andalusia (southern Spain). Several physiological parameters, including predawn xylem water potentials and relative water content in soil, roots, and leaves as well as maximum quantum efficiency and yield of PSII were evaluated for 28 days in both irrigated and nonirrigated seedlings. The leaf proteome map of the two provenances that show the extreme responses (Seville, GSE, is the most susceptible, while Almer??a, SSA, is the least susceptible) was obtained. Statistically significant variable spots among provenances and treatments were subjected to MALDI-TOF/TOF-MS/MS analysis for protein identification. In response to drought stress, ?12.4% of the reproducible spots varied significantly depending on the treatment and the population. These variable proteins were mainly chloroplastic and belonged to the metabolism and defense/stress functional categories. The 2-DE protein profile of nonirrigated seedlings was similar in both provenances. Physiological and proteomics data were generally in good agreement. The general trend was a decrease in protein abundance upon water withholding in both provenances, mainly in those involved in ATP synthesis and photosynthesis. This decrease, moreover, was most marked in the most susceptible population compared with the less susceptible one.
From Duplicate 2 (Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galván, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V)
Keywords: Analysis of Variance; biomass; Chlorophyll ﬂuorescence; drought stress in Holm oak; Droughts; Electrophoresis; Gel; Gene Expression Regulation; Holm oak proteomics; Physiological; Physiological: genetics; Physiological: physiology; Plant; Plant Leaves; Plant Leaves: genetics; Plant Leaves: metabolism; Plant Proteins; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: genetics; Quercus: metabolism; Quercus: physiology; Seedling; Seedling: growth & development; Seedling: metabolism; Spain; Stress; Tandem mass spectrometry; Two-Dimensional; water potential

QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia (Plant Physiology and Biochemistry, 2013)
Abstract Cork oak is an economically important forest species showing a great tolerance to high temperatures and shortage of water. However, the mechanisms underlying this plasticity are still poorly understood. Among the stress regulators, transcription factors (TFs) are especially important since they can control a wide range of stress-inducible genes, which make them powerful targets for genetic engineering of stress tolerance. Here we evaluated the influence of increasing temperatures (up to 55 °C) or drought (18% field capacity, FC) on the expression profile of an R2R3-MYB transcription factor of cork oak, the QsMYB1. QsMYB1 was previously identified as being preferentially expressed in cork tissues and as having an associated alternative splicing mechanism, which results in two different transcripts (QsMYB1.1 and QsMYB1.2). Expression analysis by reverse transcription quantitative PCR (RT-qPCR) revealed that increasing temperatures led to a gradual down-regulation of QsMYB1 transcripts with more effect on QsMYB1.1 abundance. On the other hand, under drought condition, expression of QsMYB1 variants, mainly the QsMYB1.2, was transiently up-regulated shortly after the stress imposition. Recovery from each stress has also resulted in a differential response by both QsMYB1 transcripts. Several physiological and biochemical parameters (plant water status, chlorophyll fluorescence, lipid peroxidation and proline content) were determined in order to monitor the plant performance under stress and recovery. In conclusion, this report provides the first evidence that QsMYB1 TF may have a putative function in the regulatory network of cork oak response to heat and drought stresses and during plant recovery.
From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)From Duplicate 1 (QsMYB1 expression is modulated in response to heat and drought stresses and during plant recovery in Quercus suber - Almeida, Tânia; Pinto, Glória; Correia, Barbara; Santos, Conceição; Gonçalves, Sónia)The following values have no corresponding Zotero field: publisher: Elsevier Masson SAS accession-num: 24161757
Keywords: Abiotic stress; Adaptation; Cork oak; Droughts; Gene expression; Gene Expression Regulation; Genes; Hot Temperature; Physiological; Plant; Plant Bark; Plant Proteins; Plant Proteins: genetics; Plant Proteins: metabolism; Quercus; Quercus: genetics; Quercus: metabolism; R2R3-MYB; Recovery; RNA Splicing; Stress; Transcription Factors; Transcription Factors: genetics; Transcription Factors: metabolism; water

Molecular characterization of Quercus suber MYB1, a transcription factor up-regulated in cork tissues - Almeida, Tânia; Menéndez, Esther; Capote, Tiago; Ribeiro, Teresa; Santos, Conceição; Gonçalves, Sónia (Journal of Plant Physiology, 2012)
The molecular processes associated with cork development in Quercus suber L. are poorly understood. A previous molecular approach identiﬁed a list of genes potentially important for cork formation and differentiation, providing a new basis for further molecular studies. This report is the ﬁrst molecular characterization of one of these candidate genes, QsMYB1, coding for an R2R3-MYB transcription factor. The R2R3-MYB gene sub-family has been described as being involved in the phenylpropanoid and lignin pathways, both involved in cork biosynthesis. The results showed that the expression of QsMYB1 is putatively mediated by an alternative splicing (AS) mechanism that originates two different transcripts (QsMYB1.1 and QsMYB1.2), differing only in the 5 -untranslated region, due to retention of the ﬁrst intron in one of the variants. Moreover, within the retained intron, a simple sequence repeat (SSR) was identiﬁed. The upstream regulatory region of QsMYB1 was extended by a genome walking approach, which allowed the identiﬁcation of the putative gene promoter region. The relative expression pattern of QsMYB1 transcripts determined by reverse transcription quantitative polymerase chain reaction (RTqPCR) revealed that both transcripts were up-regulated in cork tissues; the detected expression was several times higher in newly formed cork harvested from trees producing virgin, second or reproduction cork when compared with wood. Moreover, the expression analysis of QsMYB1 in several Q. suber organs showed very low expression in young branches and roots, whereas in leaves, immature acorns or male ﬂowers, no expression was detected. These preliminary results suggest that QsMYB1 may be related to secondary growth and, in particular, with the cork biosynthesis process with a possible alternative splicing mechanism associated with its regulatory function.
The following values have no corresponding Zotero field: accession-num: 23218545
Keywords: Alternative Splicing; Amino Acid Sequence; Cork biosynthesis; Cork oak; Gene Expression Regulation; Genes; Lipids; Lipids: biosynthesis; Molecular Sequence Data; phellogen; Plant; Plant Bark; Plant Bark: genetics; Plant Bark: metabolism; Plant Growth Regulators; Plant Growth Regulators: biosynthesis; Plant Proteins; Plant Proteins: chemistry; Plant Proteins: metabolism; Quercus; Quercus: genetics; Quercus: metabolism; R2R3-MYB; RNA; Transcription Factors; Transcription Factors: chemistry; Transcription Factors: metabolism; Up-Regulation

Proteomic analysis of Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) pollen. - Valero Galván, José; Valledor, Luis; González Fernandez, Raquel; Navarro Cerrillo, Rafael M; Jorrín-Novo, Jesús V (Journal of proteomics, 2012)
This paper presents an analysis of Holm oak pollen proteome, together with an evaluation of the potentiality that a proteomic approach may have in the provenance variability assessment. Proteins were extracted from pollen of four Holm oak provenances, and they were analyzed by gel-based (1- and 2-DE in combination with MALDI-TOF/TOF) and gel-free (nLC-LTQ Orbitrap MS) approaches. A comparison of 1- and 2-DE protein profiles of the four provenances revealed significant differences, both qualitative and quantitative, in abundance (18 bands and 16 spots, respectively). Multivariate statistical analysis carried out on bands and spots clearly showed distinct associations between provenances, which highlight their geographical origins. A total of 100 spots selected from the 402 spots observed on 2-DE gels were identified by MALDI-TOF/TOF. Moreover, a complementary gel-free shotgun approach was performed by nLC-LTQ Orbitrap MS. The identified proteins were classified according to biological processes, and most proteins in both approaches were related to metabolism and defense/stress processes. The nLC-LTQ Orbitrap MS analysis allowed us the identification of proteins belonging to the cell wall and division, transport and translation categories. Besides providing the first reference map of Holm oak pollen, our results confirm previous studies based on morphological observations and acorn proteomic analysis. Moreover, our data support the valuable use of proteomic techniques as phylogenetic tool in plant studies.
Keywords: Electrophoresis, Gel, Two-Dimensional; Electrophoresis, Gel, Two-Dimensional: methods; Electrophoresis, Polyacrylamide Gel; phylogeny; Plant Proteins; Plant Proteins: analysis; pollen; Pollen: chemistry; Proteome; Proteome: analysis; Proteomics; Proteomics: methods; Quercus; Quercus: genetics; Quercus: metabolism; Spain; Spectrometry, Mass, Matrix-Assisted Laser Desorpti; Two-Dimensional Difference Gel Electrophoresis

Studies of variability in Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) through acorn protein profile analysis. - Valero Galván, José; Valledor, Luis; Navarro Cerrillo, Rafael M; Gil Pelegrín, Eustaquio; Jorrín-Novo, Jesús V (Journal of proteomics, 2011)
Studies of variability in Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.), the dominant tree species in the typical Mediterranean forest, have been carried out by using electrophoresis-based proteomic analysis of acorns. Ten populations distributed throughout the Andalusia region have been surveyed. Acorns were sampled from individual trees and proteins extracted from seed flour by using the TCA-acetone precipitation protocol. Extracts were subjected to SDS-PAGE and 2-DE for protein separation, gel images captured, spot or bands quantified, and subjected to statistical analysis (ANOVA, SOM and clustering). Variable bands or spots among populations were subjected to MALDI-TOF/TOF and LC-MS/MS for identification. The protein yield of the used protocol varied among populations, and it was in the 2.92-5.92 mg/g dry weight range. A total of 23 bands were resolved by SDS-PAGE in the 3-35 kDa Mr range, with 8 and 12, out of the total, showing respectively qualitative and quantitative statistically significant differences among populations. Data allowed grouping populations, with groups being correlated according to geographical location and climate conditions, to northern and southern, as well as the discrimination of both mesic and xeric groups. Acorn flour extracts from the most distant populations were analyzed by 2-DE, and 56 differential spots were proposed as markers of variability. Identified proteins were classified into two principal categories; storage and stress/defense protein. Besides providing the first reference map of mature acorn seeds, the use of SDS-PAGE and proteomics in characterizing natural biodiversity in forest trees will be discussed.
Keywords: Acorn proteomics; Chromatography; Electrophoresis; Gene Expression Profiling; Holm oak variability; Liquid; Mass; Matrix-Assisted Laser Desorpti; Plant Proteins; Plant Proteins: metabolism; Polyacrylamide Gel; Quercus; Quercus ilex proteomics; Quercus: genetics; Quercus: metabolism; Seeds; Seeds: chemistry; Spectrometry; Tandem mass spectrometry

Tropospheric ozone effects on chemical composition and decomposition rate of Quercus ilex L. leaves. - Baldantoni, Daniela; Fagnano, Massimo; Alfani, Anna (The Science of the total environment, 2011)
We determined the effects of tropospheric ozone on the chemical composition of Quercus ilex L. leaves and their decomposition, with a view to assessing the influence of ozone on nutrient cycling and the sustainability of Mediterranean holm oak forests. Forming one of the most widespread thermophilous vegetation communities in the area, Q. ilex is a dominant and widespread evergreen oak in the Mediterranean, where concentrations of tropospheric ozone are particularly high. The dynamics of carbon, nitrogen, lignin and cellulose concentrations were monitored for six months during the decomposition of leaves from plants subjected to controlled ozone exposure in open-top chambers. Ozone-exposed leaves, compared to unexposed leaves, showed no significant differences in C, N, lignin and cellulose concentrations prior to the incubation in mesocosms. However, during decomposition, leaves from plants exposed to ozone lost C significantly more slowly and showed a higher C/N ratio than unexposed leaves. Ozone exposure significantly slowed down the decomposition rate, indicating a negative effect of tropospheric ozone on nutrient cycling, which may reduce long-term sustainability of the holm oak forest.
Keywords: Air Pollutants; Air Pollutants: chemistry; Air Pollutants: metabolism; Air Pollutants: toxicity; Atmosphere; Atmosphere: chemistry; Carbon; carbon cycle; Carbon: analysis; Carbon: metabolism; Cellulose; Cellulose: analysis; Cellulose: metabolism; Decaying leaf composition; Holm oak leaves; Lignin; Lignin: analysis; Lignin: metabolism; Mediterranean area; nitrogen; nitrogen cycle; Nitrogen: analysis; Nitrogen: metabolism; Ozone; ozone exposure; Ozone: chemistry; Ozone: metabolism; Ozone: toxicity; Plant Leaves; Plant Leaves: chemistry; Plant Leaves: metabolism; Quercus; Quercus: chemistry; Quercus: metabolism

Changes in water content and distribution in Quercus ilex leaves during progressive drought assessed by in vivo 1H magnetic resonance imaging. - Sardans, Jordi; Penuelas, Josep; Lope-Piedrafita, Silvia (BMC plant biology, 2010)
Drought is a common stressor in many regions of the world and current climatic global circulation models predict further increases in warming and drought in the coming decades in several of these regions, such as the Mediterranean basin. The changes in leaf water content, distribution and dynamics in plant tissues under different soil water availabilities are not well known. In order to fill this gap, in the present report we describe our study withholding the irrigation of the seedlings of Quercus ilex, the dominant tree species in the evergreen forests of many areas of the Mediterranean Basin. We have monitored the gradual changes in water content in the different leaf areas, in vivo and non-invasively, by 1H magnetic resonance imaging (MRI) using proton density weighted (rhow) images and spin-spin relaxation time (T2) maps.
From Duplicate 1 ( Changes in water content and distribution in Quercus ilex leaves during progressive drought assessed by in vivo 1H magnetic resonance imaging. - Sardans, Jordi; Peñuelas, Josep; Lope-Piedrafita, Silvia )
Keywords: Droughts; Magnetic Resonance Imaging; Physiological; Plant Leaves; Plant Leaves: metabolism; Quercus; Quercus: metabolism; Seedling; Seedling: metabolism; Soil; Soil: analysis; Stress; Time Factors; water; Water: metabolism (citation)

Remobilization of acorn nitrogen for seedling growth in holm oak (Quercus ilex), cultivated with contrasting nutrient availability. - Villar-Salvador, Pedro; Heredia, Norberto; Millard, Peter (Tree physiology, 2010)
The relative contribution of nitrogen (N) reserves from seeds or uptake by the roots to the growth and N content of young seedlings has received little attention. In this study, we investigated the contribution of N from the acorn or uptake by the roots to the N content of holm oak (Quercus ilex L.) seedlings and determined if remobilization of acorn N was affected by nutrient availability in the growing media. Q. ilex seedlings were cultivated for 3 months, until the end of the second shoot flush of growth, with three N fertilization rates: 8.6 mM N, 1.4 mM N or no fertilization. Fertilizer N was enriched in (15)N. Between 62 and 75% of the N contained in high and low fertilized seedlings, respectively, at the end of the second flush of growth was derived from the acorn. However, the dependence on acorn N was greater during the early root growth and first shoot flush of growth and decreased during the second shoot flush of growth, with root uptake contributing 32-54% of plant new N in this latter developmental stage in high and low fertilized plants, respectively. Fertilization rate did not affect the amount of N taken up during the earliest developmental stages, but it increased it during the second shoot flush of growth. Fertilization increased the mass of the shoot segment formed during the second shoot flush of growth and reduced the root mass, with no effect on whole plant growth. Remobilization of acorn N was faster in unfertilized plants than in fertilized plants. It is concluded that the holm oak seedlings depend greatly upon acorn N until the end of the second shoot flush of growth, that significant root N uptake starts at the beginning of the second shoot flush of growth and that acorn N remobilization is a plastic process that is accelerated under extremely low substratum nutrient content.
Keywords: germination; nitrogen; Nitrogen Isotopes; Nitrogen Isotopes: metabolism; Nitrogen: metabolism; Quercus; Quercus: growth & development; Quercus: metabolism; Seedling; Seedling: growth & development; Seedling: metabolism; Seeds; Seeds: metabolism; Soil

Modelling the drought impact on monoterpene fluxes from an evergreen Mediterranean forest canopy. - Grote, Rüdiger; LAVOIR, ANNE-VIOLETTE; Rambal, Serge; Staudt, Michael; Zimmer, Ina; Schnitzler, Jörg-Peter (Oecologia, 2009)
In many ecosystems drought cycles are common during the growing season but their impact on volatile monoterpene emissions is unclear. Therefore, we aimed to develop and evaluate a process-based modelling approach to explore the explanatory power of likely mechanisms. The biochemically based isoprene and monoterpene emission model SIM-BIM2 has been modified and linked to a canopy model and a soil water balance model. Simulations are carried out for Quercus ilex forest sites and results are compared to measured soil water, photosynthesis, terpene-synthase activity, and monoterpene emission rates. Finally, the coupled model system is used to estimate the annual drought impact on photosynthesis and emission. The combined and adjusted vegetation model was able to simulate photosynthesis and monoterpene emission under dry and irrigated conditions with an R(2) of 0.74 and 0.52, respectively. We estimated an annual reduction of monoterpene emission of 67% for the extended and severe drought period in 2006 in the investigated Mediterranean ecosystem. It is concluded that process-based ecosystem models can provide a useful tool to investigate the involved mechanisms and to quantify the importance of specific environmental constraints.
Keywords: Biological; Carbon dioxide; Carbon Dioxide: metabolism; Computer Simulation; Drought impact; Droughts; France; Model coupling; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: physiology; Plant Leaves; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: metabolism; Scaling; Trees; Trees: metabolism; water; Water: metabolism

Proteomic analysis from haploid and diploid embryos of Quercus suber L. identifies qualitative and quantitative differential expression patterns. - Gómez, Aranzazu; López, Juan Antonio; Pintos, Beatriz; Camafeita, Emilio; Bueno, Ma Angeles (Proteomics, 2009)
Quercus suber L. is a Mediterranean forest species with ecological, social and economic value. Clonal propagation of Q. suber elite trees has been successfully obtained from in vitro-derived somatic and gametic embryos. These clonal lines play a main role in breeding and genetic studies of Q. suber. To aid in unravelling diverse genetic and biological unknowns, a proteomic approach is proposed. The proteomic analysis of Q. suber somatic and gametic in vitro culture-derived embryos, based on DIGE and MALDI-MS, has produced for the first time proteomic data on this species. Seventeen differentially expressed proteins have been identified which display significantly altered levels between gametic and somatic embryos. These proteins are involved in a variety of cellular processes, most of which had been neither previously associated with embryo development nor identified in the genus Quercus. Some of these proteins are involved in stress and pollen development and others play a role in the metabolism of tannins and phenylpropanoids, which represent two of the major pathways for the synthesis of cork chemical components. Furthermore, the augmented expression levels found for specific proteins are probably related to the homozygous state of a doubled-haploid sample. Proteins involved in synthesis of cork components can be detected at such early stages of development, showing the potential of the method to be useful in searching for biomarkers related to cork quality.
Keywords: cluster analysis; Cork oak; Diploidy; Electrophoresis; Embryonic Development; flow cytometry; Gametic embryogenesis; Gel; Haploid and diploid embryos; Haploidy; Plant Proteins; Plant Proteins: analysis; Plant Proteins: biosynthesis; Plant Proteins: genetics; Plant proteomics; Ploidies; Ploidy level; Principal component analysis; Proteomics; Proteomics: methods; Quercus; Quercus suber L.; Quercus: chemistry; Quercus: genetics; Quercus: metabolism; Seeds; Seeds: chemistry; Seeds: genetics; Seeds: metabolism; Two-Dimensional; Up-Regulation

Geophysical imaging of root-zone, trunk, and moisture heterogeneity - Attia Al Hagrey, Said (Journal of Experimental Botany, 2007)
The most significant biotic and abiotic stress agents of water extremity, salinity, and infection lead to wood decay and modifications of moisture and ion content, and density. This strongly influences the (di-)electrical and mechanical properties and justifies the application of geophysical imaging techniques. These are less invasive and have high resolution in contrast to classical methods of destructive, single-point measurements for inspecting stresses in trees and soils. This review presents some in situ and in vivo applications of electric, radar, and seismic methods for studying water status and movement in soils, roots, and tree trunks. The electrical properties of a root-zone are a consequence of their moisture content. Electrical imaging discriminates resistive, woody roots from conductive, soft roots. Both types are recognized by low radar velocities and high attenuation. Single roots can generate diffraction hyperbolas in radargrams. Pedophysical relationships of water content to electrical resistivity and radar velocity are established by diverse infiltration experiments in the field, laboratory, and in the full-scale ‘GeoModel’ at Kiel University. Subsurface moisture distributions are derived from geophysical attribute models. The ring electrode technique around trunks images the growth ring structure of concentric resistivity, which is inversely proportional to the fluid content. Healthy trees show a central high resistivity within the dry heartwood that strongly decreases towards the peripheral wet sapwood. Observed structural deviations are caused by infection, decay, shooting, or predominant light and/or wind directions. Seismic trunk tomography also differentiates between decayed and healthy woods.
10.1093/jxb/erl237
Keywords: Electric Impedance; Electrical resistivity techniques; Electrodes; Geological Phenomena; Geology; Plant Roots; Plant Roots: metabolism; Populus; Populus: physiology; Portugal; Quercus; Quercus: anatomy & histology; Quercus: metabolism; Radar; radar imaging; ring electrode array; root-zone; sap flow; seismic tomography; trunk ring structure; vadose zone; water; water content; water flow; Water: analysis; Water: metabolism

Geophysical imaging of root-zone, trunk, and moisture heterogeneity - Attia Al Hagrey, Said (Journal of Experimental Botany, 2007)
The most significant biotic and abiotic stress agents of water extremity, salinity, and infection lead to wood decay and modifications of moisture and ion content, and density. This strongly influences the (di-)electrical and mechanical properties and justifies the application of geophysical imaging techniques. These are less invasive and have high resolution in contrast to classical methods of destructive, single-point measurements for inspecting stresses in trees and soils. This review presents some in situ and in vivo applications of electric, radar, and seismic methods for studying water status and movement in soils, roots, and tree trunks. The electrical properties of a root-zone are a consequence of their moisture content. Electrical imaging discriminates resistive, woody roots from conductive, soft roots. Both types are recognized by low radar velocities and high attenuation. Single roots can generate diffraction hyperbolas in radargrams. Pedophysical relationships of water content to electrical resistivity and radar velocity are established by diverse infiltration experiments in the field, laboratory, and in the full-scale ‘GeoModel’ at Kiel University. Subsurface moisture distributions are derived from geophysical attribute models. The ring electrode technique around trunks images the growth ring structure of concentric resistivity, which is inversely proportional to the fluid content. Healthy trees show a central high resistivity within the dry heartwood that strongly decreases towards the peripheral wet sapwood. Observed structural deviations are caused by infection, decay, shooting, or predominant light and/or wind directions. Seismic trunk tomography also differentiates between decayed and healthy woods.
10.1093/jxb/erl23710.1093/jxb/erl237The following values have no corresponding Zotero field: accession-num: 17229759
Keywords: Electric Impedance; Electrical resistivity techniques; Electrodes; Geological Phenomena; Geology; Plant Roots; Plant Roots: metabolism; Populus; Populus: physiology; Portugal; Quercus; Quercus: anatomy & histology; Quercus: metabolism; Radar; radar imaging; ring electrode array; root-zone; sap flow; seismic tomography; trunk ring structure; vadose zone; water; water content; water flow; Water: analysis; Water: metabolism

Sensitivity of volatile monoterpene emission to changes in canopy structure: a model-based exercise with a process-based emission model - Grote, Rüdiger (New Phytologist, 2007)
* • This paper investigates the dependence of monoterpene emissions at the canopy scale on total leaf area and leaf distribution. Simulations were carried out for a range of hypothetical but realistic forest canopies of the evergreen Quercus ilex (holm oak). * • Two emission models were applied that either did (SIM-BIM2) or did not (G93) account for cumulative responses to temperature and light. Both were embedded into a canopy model that considered spatial and temporal variations of foliage properties. This canopy model was coupled to a canopy climate model (CANOAK) to determine the micrometeorological conditions at the leaf scale. * • Structural properties considerably impacted monoterpene emission. The sensitivities to changes in total leaf area and to leaf area distribution were found to be of similar magnitude. The two different models performed similarly on a whole-year basis but showed clear differences during certain episodes. * • The analysis showed that structural indices have to be carefully evaluated for proper scaling of emission from leaves to canopy. Further research is encouraged on seasonal dynamics of emission potentials.
Keywords: Biological; biomass; foliage distribution; leaf area index; light; Models; monoterpene emission; Monoterpenes; Monoterpenes: metabolism; photosynthesis; Photosynthesis: radiation effects; Plant Leaves; Plant Leaves: metabolism; Plant Leaves: radiation effects; Quercus; Quercus ilex; Quercus: metabolism; Quercus: radiation effects; Scaling; stand density; Temperature; Time Factors; Volatilization

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd accession-num: 16390425
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Dynamics of the enhanced emissions of monoterpenes and methyl salicylate, and decreased uptake of formaldehyde, by Quercus ilex leaves after application of jasmonic acid - Filella, Iolanda; Penuelas, Josep; Llusia, Joan (New Phytologist, 2006)
* • Jasmonic acid (JA) is a signalling compound with a key role in both stress and development in plants, and is reported to elicit the emission of volatile organic compounds (VOCs). Here we studied the dynamics of such emissions and the linkage with photosynthetic rates and stomatal conductance. * • We sprayed JA on leaves of the Mediterranean tree species Quercus ilex and measured the photosynthetic rates, stomatal conductances, and emissions and uptake of VOCs using proton transfer reaction mass spectrometry and gas chromatography after a dark–light transition. * • Jasmonic acid treatment delayed the induction of photosynthesis and stomatal conductance by approx. 20 min, and decreased them 24 h after spraying. Indications were found of both stomatal and nonstomatal limitations of photosynthesis. Monoterpene emissions were enhanced (20–30%) after JA spraying. Jasmonic acid also increased methyl salicylate (MeSa) emissions (more than twofold) 1 h after treatment, although after 24 h this effect had disappeared. Formaldehyde foliar uptake decreased significantly 24 h after JA treatment. * • Both biotic and abiotic stresses can thus affect plant VOC emissions through their strong impact on JA levels. Jasmonic acid-mediated increases in monoterpene and MeSa emissions might have a protective role when confronting biotic and abiotic stresses.
Keywords: Carbon dioxide; Carbon Dioxide: metabolism; Cyclopentanes; Cyclopentanes: pharmacology; Dehydration; Formaldehyde; Formaldehyde: metabolism; jasmonic acid (JA); light; methyl salicylate; Monoterpenes; Monoterpenes: metabolism; net photosynthetic rates; Oxylipins; photosynthesis; Plant Leaves; Plant Leaves: drug effects; Plant Leaves: metabolism; Quercus; Quercus ilex (holm oak); Quercus: drug effects; Quercus: metabolism; Salicylates; Salicylates: metabolism; Stomatal conductance; Temperature; VOC (volatile organic compound)

Variation in the holm oak leaf proteome at different plant developmental stages, between provenances and in response to drought stress. - Jorge, Inmaculada; Navarro, Rafael M; Lenz, Christof; Ariza, David; Jorrín, Jesús (Proteomics, 2006)
Major proteins of the holm oak leaf proteome have been previously identified using a combination of 2-DE, MS analysis and BLAST similarity search (Jorge et al., Proteomics 2005, 5, 222-234). That study, conducted with field samples from mature trees, revealed the existence of a great variability in the 2-DE protein map, with qualitative as well as quantitative changes, both analytical and biological. A similar study has been carried out with 2-year-old seedlings to analyze and study: (i) changes in the 2-DE protein profile at different tree developmental stages; (ii) the 2-DE protein map variability between three different Spanish provenances; and (iii) variations in the 2-DE protein profile in response to drought stress. Although the protein profile of leaves from seedlings and mature trees was fairly similar, the biological variance found was lower in the former. In the present study, new proteins have been identified. At least four different protein spots differentiated Spanish provenances, two of them identified as an ATP synthase alpha chain, and a 2,3-bisphosphoglycerate-independent phosphoglycerate mutase. Fourteen different protein spots were qualitatively variable between well-watered and drought-stressed seedlings, with some of them corresponding to enzymes of carbohydrate and protein metabolism. Data presented indicated the mobilization of storage proteins and carbohydrates, as well as photosynthesis inhibition under drought conditions.
Keywords: Dehydration; Dehydration: metabolism; Disasters; Electrophoresis, Gel, Two-Dimensional; Plant Leaves; Plant Leaves: metabolism; Proteome; Proteome: metabolism; Proteomics; Quercus; Quercus: embryology; Quercus: metabolism; Seedling; Seedling: metabolism

Changes in pectins and MAPKs related to cell development during early microspore embryogenesis in Quercus suber L. - Ramírez, Carmen; Testillano, Pilar S; Pintos, Beatriz; Moreno-Risueño, Miguel a; Bueno, María a; Risueño, María C (European journal of cell biology, 2004)
The occurrence and significance of changes in cell wall components and signalling molecules has been investigated during early microspore embryogenesis in cork oak (Quercus suber L.) in relation to cell proliferation and cell differentiation. Microspore embryogenesis has been induced in in vitro anther cultures of Q. suber by the application of a stress treatment of 33 degrees C. After the treatment, microspores at the responsive developmental stage of vacuolate microspore switched towards proliferation and the embryogenesis pathway to further produce haploid plantlets. Ultrastructural and immunocytochemical analysis revealed changes in cell organisation after induction at different developmental stages, the cellular features displayed being in relation to the activation of proliferative activity and the beginning of differentiation in young and late proembryos. Immunogold labelling with JIM5 and JIM7 antibodies showed a different presence of pectin and level of its esterification in cell walls at different developmental stages. Non-esterified pectins were found in higher proportions in cells of late proembryos, suggesting that pectin de-esterification could be related to the beginning of differentiation. The presence and subcellular distribution of Erk 1/2 MAPK homologues have been investigated by immunoblotting, immunofluorescence and immunogold labelling. The results showed an increase in the expression of these proteins with a high presence in the nucleus, during early microspore proembryos development. The reported changes during early microspore embryogenesis are modulated in relation to proliferation and differentiation events. These findings provided new evidences for a role of MAPK signalling pathways in early microspore embryogenesis, specifically in proliferation, and would confer information for the cell fate and the direction of the cell development.
Keywords: Cell Differentiation; Cell Differentiation: physiology; Electron; MAPKs; Microscopy; microspore embryogenesis; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 1: metabolism; Mitogen-Activated Protein Kinase 3; Mitogen-Activated Protein Kinase 3: metabolism; Mitogen-Activated Protein Kinases; Mitogen-Activated Protein Kinases: metabolism; Pectins; Pectins: metabolism; Proliferation; Quercus; Quercus: embryology; Quercus: enzymology; Quercus: metabolism; Seeds; Seeds: cytology; Seeds: ultrastructure

Changes in pectins and MAPKs related to cell development during early microspore embryogenesis in Quercus suber L. - Ramírez, Carmen; Testillano, Pilar S.; Pintos, Beatriz; Moreno-Risueño, Miguel a; Bueno, María a; Risueño, María C. (European journal of cell biology, 2004)
The occurrence and significance of changes in cell wall components and signalling molecules has been investigated during early microspore embryogenesis in cork oak (Quercus suber L.) in relation to cell proliferation and cell differentiation. Microspore embryogenesis has been induced in in vitro anther cultures of Q. suber by the application of a stress treatment of 33 degrees C. After the treatment, microspores at the responsive developmental stage of vacuolate microspore switched towards proliferation and the embryogenesis pathway to further produce haploid plantlets. Ultrastructural and immunocytochemical analysis revealed changes in cell organisation after induction at different developmental stages, the cellular features displayed being in relation to the activation of proliferative activity and the beginning of differentiation in young and late proembryos. Immunogold labelling with JIM5 and JIM7 antibodies showed a different presence of pectin and level of its esterification in cell walls at different developmental stages. Non-esterified pectins were found in higher proportions in cells of late proembryos, suggesting that pectin de-esterification could be related to the beginning of differentiation. The presence and subcellular distribution of Erk 1/2 MAPK homologues have been investigated by immunoblotting, immunofluorescence and immunogold labelling. The results showed an increase in the expression of these proteins with a high presence in the nucleus, during early microspore proembryos development. The reported changes during early microspore embryogenesis are modulated in relation to proliferation and differentiation events. These findings provided new evidences for a role of MAPK signalling pathways in early microspore embryogenesis, specifically in proliferation, and would confer information for the cell fate and the direction of the cell development.
The following values have no corresponding Zotero field: accession-num: 15346811
Keywords: Cell Differentiation; Cell Differentiation: physiology; Electron; MAPKs; Microscopy; microspore embryogenesis; Mitogen-Activated Protein Kinase 1; Mitogen-Activated Protein Kinase 1: metabolism; Mitogen-Activated Protein Kinase 3; Mitogen-Activated Protein Kinase 3: metabolism; Mitogen-Activated Protein Kinases; Mitogen-Activated Protein Kinases: metabolism; Pectins; Pectins: metabolism; Proliferation; Quercus; Quercus: embryology; Quercus: enzymology; Quercus: metabolism; Seeds; Seeds: cytology; Seeds: ultrastructure